GCMS-based phytochemical profiling and in vitro pharmacological activities of plant Alangium salviifolium (L.f) Wang - Annapurneshwari M. Hongal; Arun K. Shettar; Joy H. Hoskeri; A. B. Vedamurthy (SpringerOpen, 2024)
Abstract Background There is an urge for traditional herbal remedies as an alternative to modern medicine in treating several diseases. A significant number of modern pharmaceutical drugs are based on or derived from medicinal plants or their extracts. These drugs derived from the plant origin have various antimicrobial, antioxidant, anticancer, anti-inflammatory activities. Alangium salviifolium belongs to Cornaceae family and is well known for its medicinal properties. The present study was carried out to evaluate the antibacterial, antioxidant effect and possible bioactive components present in the chloroform, acetone, ethanol, methanol and aqueous extract of Alangium salviifolium leaves. Methodology Dried leaves of Alangium salviifolium were subjected to serial solvent extraction using increasing polarity of solvents, i.e., chloroform, acetone, methanol, ethanol, and distilled water. Crude extracts were further tested for qualitative analysis of phytochemicals using standard procedure, while GCMS analysis was performed to identify the probable phytocompounds. Antibacterial activity was performed against bacterial pathogens using agar well method, whereas antioxidant activity was performed using in vitro PM, DPPH and FRAP assays. Results Phytochemical analysis of the extracts revealed the presence of key phytochemical classes. Using gas chromatography-mass spectrometry, several high and low molecular weight chemical compound kinds were discovered. These chemical substances are regarded as having significant biological and pharmacological effects. All crude extracts had considerable and comparable in vitro antioxidant and antibacterial properties. Conclusions According to the findings of this study, Alangium salviifolium leaves are a rich source of phytoconstituents that are crucial in stopping the advancement of numerous disorders.